Cancer targeting by TCR gene-engineered T cells directed against Kita-Kyushu Lung Cancer Antigen-1. Issue 1 (28th August 2019) - Marcinkowski, Bridget; Stevanović, Sanja; Helman, Sarah R.; Norberg, Scott M.; Serna, Carylinda; Jin, Benjamin; Gkitsas, Nikolaos; Kadakia, Tejas; Warner, Andrew; Davis, Jeremy L.; Rooper, Lisa; Hinrichs, Christian S.
Abstract : T cell receptor (TCR) gene-engineered T cells have shown promise in the treatment of melanoma and synovial cell sarcoma, but their application to epithelial cancers has been limited. The identification of novel therapeutic TCRs for the targeting of these tumors is important for the development of new treatments. Here, we describe the preclinical characterization of a TCR directed against Kita-Kyushu Lung Cancer Antigen-1 (KK-LC-1, encoded by CT83 ), a cancer germline antigen with frequent expression in human epithelial malignancies including gastric cancer, breast cancer, and lung cancer. Gene-engineered T cells expressing the KK-LC-1 TCR (KK-LC-1 TCR-Ts) demonstrated recognition of CT83 + tumor lines in vitro and mediated regression of established CT83+ xenograft tumors in immunodeficient mouse models. Cross-reactivity studies based on experimental determination of the recognition motifs for the target epitope did not demonstrate cross-reactivity against other human proteins. CT83 gene expression studies in 51 non-neural tissues and 24 neural tissues showed expression restricted exclusively to germ cells. CT83 was however expressed by a range of epithelial cancers, with the highest expression noted in gastric cancer. Collectively, these findings support the further investigation and clinical testing of KK-LC-1 TCR-Ts for gastric cancer and possibly other malignancies.